2014
DOI: 10.1002/ece3.1198
|View full text |Cite
|
Sign up to set email alerts
|

Historical land‐use and landscape change in southern Sweden and implications for present and future biodiversity

Abstract: The two major aims of this study are (1) To test the performance of the Landscape Reconstruction Algorithm (LRA) to quantify past landscape changes using historical maps and related written sources, and (2) to use the LRA and map reconstructions for a better understanding of the origin of landscape diversity and the recent loss of species diversity. Southern Sweden, hemiboreal vegetation zone. The LRA was applied on pollen records from three small bogs for four time windows between AD 1700 and 2010. The LRA es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…This study uses the simulation-based estimates of the past RSAP-the area within a 1,740 m radius at Å bodasjön and a 1,440 m radius at Lindhultsgöl. These are similar to the estimates for Danish lakes (3-27 ha) based on historical maps in 1800 (Nielsen and Sugita 2005) and to the estimates for Småland peatbogs (same area as our study, Cui et al 2014) based on the forward modeling approach. Consistent with Nielsen and Odgaard (2010), we assume that the RSAP is constant through time for our reconstruction.…”
Section: Pollen-based Approachsupporting
confidence: 88%
See 2 more Smart Citations
“…This study uses the simulation-based estimates of the past RSAP-the area within a 1,740 m radius at Å bodasjön and a 1,440 m radius at Lindhultsgöl. These are similar to the estimates for Danish lakes (3-27 ha) based on historical maps in 1800 (Nielsen and Sugita 2005) and to the estimates for Småland peatbogs (same area as our study, Cui et al 2014) based on the forward modeling approach. Consistent with Nielsen and Odgaard (2010), we assume that the RSAP is constant through time for our reconstruction.…”
Section: Pollen-based Approachsupporting
confidence: 88%
“…A similar study in the same region (Cu 2013; Cui et al 2014) concluded that there are clear similarities between the regional estimates. Moreover, the general agreement between the LRA-and QADbased results provides confidence in the interpretation of the differences in vegetation and land-use cover between the two sites, even though some of the assumptions of both approaches are not fully satisfied.…”
Section: Pollen-based Approachmentioning
confidence: 71%
See 1 more Smart Citation
“…In bold: large lakes Veget Hist Archaeobot (2016) 25:131-151 133 of past vegetation composition have already been shown to be useful for (i) the quantitative reconstruction of vegetation/plant cover at the local spatial scale (10-100 km 2 ) using Sugita's LRA (e.g. Nielsen and Odgaard 2010;Cui et al 2013Cui et al , 2014Mazier et al 2015;Hultberg et al 2015), (ii) the study of regional spatio-temporal land-cover/landscape dynamics over the past millennia (e.g. Marquer et al 2014;Fyfe et al 2013;Nielsen et al 2012;Trondman 2014), (iii) the evaluation of anthropogenic land-cover change scenarios (ALCCs) (Gaillard et al 2010) and (iv) the study of land cover-climate interactions in the past (Strandberg et al 2014).…”
Section: Figmentioning
confidence: 99%
“…So far, estimates achieved from this approach are found to be representative of the vegetation in Denmark, Switzerland, Sweden, Estonia and Norway (Hellman et al 2008;Nielsen and Odgaard 2010;Soepboer et al 2010;Fredh 2012;Cui et al 2013;Overballe-Petersen et al 2013;Poska et al 2014;Hjelle et al 2015), and it has been applied to reconstruct vegetation cover on different spatial scales (e.g. Nielsen et al 2012;Fyfe et al 2013;Cui et al 2014;Marquer et al 2014;Hultberg et al 2015;Trondman et al 2015).…”
Section: Introductionmentioning
confidence: 99%